DDX21 is a p38-MAPK-sensitive nucleolar protein necessary for mouse preimplantation embryo development and cell-fate specification - Bora, Pablo; Gahurova, Lenka; Hauserova, Andrea; Stiborova, Martina; Collier, Rebecca; Potěšil, David; Zdráhal, Zbyněk; Bruce, Alexander W (Open biology, 2021)
Successful navigation of the mouse preimplantation stages of development, during which three distinct blastocyst lineages are derived, represents a prerequisite for continued development. We previously identified a role for p38-mitogen-activated kinases (p38-MAPK) regulating blastocyst inner cell mass (ICM) cell fate, specifically primitive endoderm (PrE) differentiation, that is intimately linked to rRNA precursor processing, polysome formation and protein translation regulation. Here, we develop this work by assaying the role of DEAD-box RNA helicase 21 (DDX21), a known regulator of rRNA processing, in the context of p38-MAPK regulation of preimplantation mouse embryo development. We show nuclear DDX21 protein is robustly expressed from the 16-cell stage, becoming exclusively nucleolar during blastocyst maturation, a localization dependent on active p38-MAPK. siRNA-mediated clonal Ddx21 knockdown within developing embryos is associated with profound cell-autonomous and non-autonomous proliferation defects and reduced blastocyst volume, by the equivalent peri-implantation blastocyst stage. Moreover, ICM residing Ddx21 knockdown clones express the EPI marker NANOG but rarely express the PrE differentiation marker GATA4. These data contribute further significance to the emerging importance of lineage-specific translation regulation, as identified for p38-MAPK, during mouse preimplantation development.
Keywords: Animals; p38 Mitogen-Activated Protein Kinases; Cell Lineage; Female; DDX21; buněčný rodokmen; Gene Expression Regulation, Developmental; ženské pohlaví; cell fate specification; blastocysta; vazba proteinů; buněčná diferenciace; Gene Knockdown Techniques; Protein Transport; fluorescenční protilátková technika; Mice; těhotenství; Fluorescent Antibody Technique; p38-MAPK; signální transdukce; DEAD-box RNA-helikasy; preimplantation embryo development; myši; mitogenem aktivované proteinkinasy p38; Signal Transduction; Blastocyst; transport proteinů; Embryonic Development; genový knockdown; Cell Differentiation; zvířata; embryonální vývoj; Pregnancy; vývojová regulace genové exprese; Protein Binding; DEAD-box RNA Helicases